(3efJNH ef GdEQTGO aj YdeGA GdHdGO dCHj jYdi Ndjd Hf YHOGddg GdNdjdj GdbRhjfj GdeJhaj SfI(B446(3g`s - (3CHhWGgQ CMeO Hf eMeO GdSdaj GdCUHgGfjs; (3CHh jYdj Ndjd Hf YHO Gddg Hf CMeO Hf EHQGgje GHf GdNdjd GdbRhjfj, GdNdjdj,J (B446 (3g` s
(3ChdgG (B:s
(3hehdi hgh PG ecMhd HGdTGe hgh ehdi , Ke bGd(B: (3EPG JbGYO CHfGA GdegGLQjf hGdCfUGQ Yf JYdje GdYde dZdHge GdehGdi, Ke bGd (B:(3CNPJ GdYde Yf s
(3BNQgG (B:s
(3hCMGOjKg JOd Ydi VYag , CNHQfG CHj hLeGYI bGdhG(B: (3MOKfG Ydi Hf EHQGgje GdbWGf, MOKfG eMeO Hf CMeO Hf eMeO Hf CejI GdSGhi HbRhjf , MOKfG CHj s
(3hgj aj YTQI CLRGA MOjKjIs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B319s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B362 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B618 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B431 s
Keywords: (3GdJGQjNs